PENINGKATAN PEREKONOMIAN MASYARAKAT DALAM PEMBERDAYAAN HUTAN MANGROVE SEBAGAI INDUSTRI EKOWISATA DI PULAU UNTUNG JAWA - Ika Widiastuti (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
The aim of community service activities is to improve the economy by providing outreach about Mangrove Forests and technical training to empower mangrove forests and community empowerment in managing the tourism industry on Untung Jawa Island. The method used is in the form of a preliminary study about mangrove forests and interviews with the community and stakeholders as well as conducting counseling, discussions and training related to the management of the tourism industry, especially Mangrove Forest ecotourism. The results of community service are planning strategies for mangrove forest processing techniques, community empowerment strategies in managing the tourism industry and identification of other potentials on Untung Jawa Island as supporting factors for the Mangrove Forest Ecotourism Industry to improve the economy of the Untung Java Island community